Peran Mediasi Citra Merek pada Pengaruh Pemasaran Sosial Media dan Ulasan Online Konsumen terhadap Minat Beli pada Generasi Z Pengguna Maybelline di Kota Makassar - Putri, Sindy Cristina; Nofri, Okta (Study of Scientific and Behavioral Management, 2023)
The purposes of this study is to determine the direct and indirect effect of social media marketing and online customer review on purchase intention with brand image as mediating variable. The type of research is correlational associative in nature, while the approach taken is quantitative one. Not less than 99 female respondents of generation z who are Maybelline users in Makassar City have taken apart in filling the questionaire. This study uses path analysis to analyze the data with the help of the SmartPLS SEM version 3. The results of this study prove that: 1) social media marketing has a positive effect on purchase intention, 2) online customer review do not have a positive effect on purchase intention, 3) social media marketing has a positive effect on brand image, 4) online customer review have a positive effect on brand image , 5) brand image has a positive effect on purchase intention, 6) social media marketing has a positive effect on purchase intention with brand image as the intervention variable, 7) online customer review have a positive effect on purchase intention with brand image as the intervention variable. Keywords: social media marketing, online customer review, purchase intention, brand image